Rosyjska i polska recepcja twórczości Romana Sienczina w latach 2001-2021 - Jastrzębska, Katarzyna (Acta Neophilologica, 2022)
This paper focuses on the Russian and Polish receptions of the works of Roman Senchin, a leading representative of the New Realism Trend in Russian literature. The writer’s debut was his collection of short stories entitled Athens Nights (Афинские ночи), published in 2000. Since then, Senchin has written many works, including The Yeltyshevs (Елтышевы), published in 2009 and translated into several languages. His works are widely commented on, discussed, analyzed, and interpreted not only by Russian literary scholars, critics, and commentators of Russian cultural life, but also by Polish researchers investigating contemporary Russian literature. The article presents the views of literary critics and literary scholars concerning Senchin’s works, as well as reflections on their typical or dominant features. Despite widely differing points of view, Russian literary critics agree that Roman Senchin is the most pessimistic contemporary Russian writer.